Financial and feasibility implications of the treatment of hepatitis C virus in Italy: scenarios and perspectives - Croce D (ClinicoEconomics and Outcomes Research, 2016)
Davide Croce,1,2 Marzia Bonfanti,1 Umberto Restelli1,2 1Center for Research on Health Economics, Social and Health Care Management, Università Cattaneo, Castellanza, Italy; 2School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South Africa Background: Hepatitis C virus (HCV) affects an estimated number of people between 130 million and 210 million worldwide. In the next few years, the Italian National Health Service will face a growing trend of patients requiring HCV antiviral treatments. The aim of the analysis was to estimate the time horizon in which it would be possible to treat HCV-infected patients and the related direct medical costs (antiviral treatment and monitoring activities) from the Italian National Health Service point of view.Methodology: In order to estimate the number of HCV-infected patients in Italy, we considered a top-down (considering published data) and a bottom-up approach. The number of years needed for treatment and related direct costs were estimated through the development of a static deterministic model.Results: The estimated number of HCV-infected patients in Italy varies from 2.7 (estimated through a top-down approach) to 0.6 million (estimated through a bottom-up approach) and 0.3 million (measured through a bottom-up approach). Considering the last two scenarios and the use of interferon-free therapies for 50,000 patients per year, treatment for HCV-infected patients could be at a cost of €13.7 billion and €7.0 billion by 2030 and 2023, respectively.Conclusion: The treatment for HCV-infected patients in Italy is a challenging target for the financial implications of patient care. HCV infection could be controlled or eliminated in a 10- to 15-year time horizon. The cost of treatment can hardly be dealt with using the traditional economic tools but should be faced through multiyear investments, as health benefits are expected in the long period. National Health Service stakeholders (industry, government, insurance, and also patients) will have to identify suitable financial instruments to face the new expenditure required. Keywords: sustainability, financial disease scenario, budget impact model